Faktor yang Berhubungan dengan Penyebab Admisi dan Kematian Pasien Systemic Lupus Erythematosus (SLE) di RSUP Prof. dr. I.G.N.G. Ngoerah, Denpasar - Ni Kadek Ariesta Dwijayanthi; Pande Ketut Kurniari (MEDICINUS, 2026)
Systemic lupus erythematosus (SLE) is a complex autoimmune disease with high mortality. Epidemiological data on SLE related mortality in Indonesia remain limited, therefore, this study was conducted to identify the characteristics of patients with SLE who died. This study used a cross-sectional design with total sampling based on medical record data of SLE patients who died during hospitalization at RSUP Prof. dr. I.G.N.G Ngoerah, Denpasar from August 2022 to October 2024. Data were analyzed using SPSS version 22.The mortality of SLE patients at RSUP Prof. dr. I.G.N.G Ngoerah, Denpasar during this study period were 45 patients. The female-to-male patient ratio was 10:1, with a mean age of 34.96 (±11.50) years, history of hospitalizations of 2,27 (±1.09) times in the last 3 months, and the length of hospitalization of 6.40 (±3.48) days. Approximately 55% of patients died within less than 3 months after the diagnosis of SLE was established. Most patients (73.33%) experienced infections, and40% patients had cardiovascular and 55.55% had renal comorbidities. Vasculitis and neuropsychiatric SLE (NPSLE) were associated with severe disease activity. While worsening SLE activity was a major factor in patient admission, deaths were primarily attributed to infections (19 cases; 42.22%) and comorbid complications (17 cases; 37.78%).Cardiovascular disease was associated with hospital admissions due to comorbid complications (p=0.05) and with increased SLE disease activity at admission (p=0.02). Infection remains the leading cause of mortality in SLE and also a contributing factor to delays in initiating high-dose corticosteroid administration. Cardiovascular disease appears to be a comorbidity that progresses and worsens earlier in SLE patients. Multidisciplinary management of infectious andcardiovascular comorbidities may reduce mortality and morbidity in SLE.